Development of mutual and intelligent water resources circulating utilization system based on image processing technology - Zheng, Zhi; Duan, Pengcheng (SPIE, 2023)
The rapid economic and social development has made people's demand for water resources increase rapidly, but at present, half of the world's rivers have been greatly reduced or seriously polluted, resulting in accelerated consumption of water resources. Therefore, the construction of a shared smart water resource recycling system is of great significance to the development of my country's current water resources management. The rapid development of computer technology provides important conditions for people to change traditional concepts and behaviors, and also provides new solutions for solving social conflicts brought about by traditional development models. Images surround humans all the time, and image processing technology replaces the work of the human eye with computers, which makes it possible for image processing technology to automate and intelligently recognize images. After continuous promotion and development, digital image processing has formed a relatively complete subject system. At present, various application fields put forward higher demands on digital image processing technology, which has promoted the development of this discipline system to a higher technical direction. This paper captures the serious problems of water shortage, pollution, waste and uneven distribution. Through the application of image processing technology in water quality analysis and detection, image processing algorithms are used for preprocessing, image segmentation, contour extraction, and the area, perimeter and other parameters for statistical analysis, and the integration of big data, deep learning and new image analysis technologies to develop intelligent platform systems. On this basis, it can not only improve the utilization efficiency of water resources, but also ensure national water security and sustainable economic and social development.